A Constitutive Model for Cemented Tailings Backfill Under Uniaxial Compression - Tu, Bingbing; Liu, Lang; Cheng, Kangli; Zhang, Bo; Zhao, Yujiao; Yang, Qixing; Song, Kiil (Frontiers in Physics, 2020)
Constitutive model is the foundation describing the mechanical properties of materials. Cemented tailings backfill (CTB) plays an important role in goaf filling. However, a universally applicable constitutive model for CTB has not been proposed yet. In this paper, a two-stage constitutive model of CTB under uniaxial compression was established, based on the Weibull distribution density function, the strain equivalence principle and the damage mechanics theory. Eight groups of CTB samples with a diameter of 50 mm and a height of 100 mm prepared with different solid contents (70-78 wt%) and cement-sand ratios (1/4-1/10) were subjected to uniaxial compression tests to verify the validity of the theoretical model. The compared results showed that the predictions of the proposed constitutive model agreed well with the experimental results. The following conclusions were also obtained: (i) Solid content and cement-sand ratio had a significant effect on the basic mechanical parameters of the CTB samples, especially at the peak stress; (ii) The constitutive model of CTB was similar to that of the ordinary cement mortar M5, but with obvious residual stress; (iii) The failure mode of the CTB specimens under uniaxial compression was mainly tensile failure. The results presented in this paper contribute to a better understanding of the uniaxial compression characteristics of CTB and lay an important foundation for future research.